Metastatic Malignant Melanoma With Complete Loss of Differentiation Markers (Undifferentiated/Dedifferentiated Melanoma): Analysis of 14 Patients Emphasizing Phenotypic Plasticity and the Value of Molecular Testing as Surrogate Diagnostic Marker - Agaimy, Abbas; Specht, Katja; Stoehr, Robert; Lorey, Thomas; Maerkl, Bruno; Niedobitek, Gerald; Straub, Melanie; Hager, Thomas; Reis, Anna-Carinna; Schilling, Bastian; Schneider-Stock, Regine; Hartmann, Arndt; et al. (American Journal of Surgical Pathology, 2016)
Metastatic malignant melanoma is notorious for its phenotypic diversity and loss of differentiation markers. We herein summarized our experience with 14 metastatic melanomas showing complete loss of immunohistochemical melanocytic markers (with or without heterologous differentiation). Patients included 11 men and 3 women aged 24 to 78 years (median, 67 y). Thirteen patients had histologically confirmed primary skin melanoma, and 1 had metastatic melanoma of unknown primary. Undifferentiated metastasis was diagnosed synchronous to primary tumor (n=1), following skin melanoma by 3 months to 9 years (n=11) and preceding it by 1 year (n=1). Sites of undifferentiated metastases were axillary (3), inguinal (1), or submandibular (1) lymph nodes, digestive tract (2), bone/soft tissue (2), lung/pleura (2), and disseminated (n=3). Histology of metastases mimicked undifferentiated pleomorphic or spindle cell sarcoma with variable myxoid and giant cell areas (n=10) and cytokeratin-positive undifferentiated small cell sarcoma (n=1). Three cases showed heterologous dedifferentiation: pleomorphic rhabdomyosarcoma (n=1), teratocarcinosarcoma-like with prominent rhabdomyoblasts (n=1), and adenocarcinoma-like with metaplastic bone (n=1). All cases were negative for S100, melanoma cocktail, HMB45, Melan A, and SOX10. Other markers showed following results: smooth muscle actin (1/14), p16 (1/14), TP53 (2/12), pancytokeratin (4/14), desmin (5/14), h-caldesmon (0/9), and MDM2/CDK4 (0/5). SMARCB1 was intact in 8/8 cases. Genotyping showed BRAF(V600E) mutation (5/14), NRAS mutation (5/14), and BRAF/NRAS wild-type (4/14). In conclusion, undifferentiated/dedifferentiated metastatic melanoma is likely underrecognized and frequently mistaken for undifferentiated sarcoma or other neoplasms. Diagnosis of undifferentiated sarcoma at sites where melanoma metastasis are frequent (eg, inguinal and axillary region) should be made with great caution and warrants exploration of the remote history. Genotyping is a helpful surrogate marker in classifying such difficult cases. In the light of available targeted therapies, recognition of undifferentiated/dedifferentiated metastatic melanoma is mandatory for appropriate treatment.
EVALuna2:6798